Conflicting Counter-Hegemonies?: The Dramaturgy of James Connolly and Sean O'Casey - Moran, James (Archīum Ateneo, 2024)
This paper examines the radicalism of James Connolly through the optic of theatre and performance. In particular, I test his only extant play-script—written shortly before his death—against the hostile critique of the dramatist Seán O’Casey. Despite the biographical similarities between these two men, O’Casey expressed deep disappointment with the climax of Connolly’s career as a labor agitator, organizer and revolutionary socialist, criticizing him for having travelled from socialism to nationalism, a journey which O’Casey had seemingly made in reverse. I offer a rereading of Connolly’s play to show that the situation is more complex than that envisaged by O’Casey. Although his dramaturgy is indebted to the nationalism of Yeats and Gregory, Connolly is eager to distance his play from the economic and social ordering endorsed by those Abbey Theatre directors. Furthermore, this essay subjects O’Casey’s own critique to revision in the light of his own later playwriting. By examining his little-known Oak Leaves and Lavender I show that O’Casey was—like Connolly—ready to endorse military action in the name of nationalism, if such action provided the hope of ultimately advancing the cause of the left. The paper concludes with some reflections on O’Casey’s late endorsement of English and Welsh nationalisms, by considering how the expression of socialism in colonized Ireland (1890-1916) might contrast with the expression of socialism among expatriate or second- generation Irish men and women in wartime/post-war Britain (1939 onwards). I therefore finish by examining the work of the Connolly Association, the plays of Margaretta D’Arcy and John Arden, and genesis of The Dubliners’ 1970 LP, Revolution, to show how—as the twentieth century continued—the expression of Irish socialism may have continued to develop through contact with very different kinds of national sentiment.